INDEPENDENSI SISTEM PERADILAN MILITER DI INDONESIA (Studi Tentang Struktur Peradilan Militer) - Edy, Slamet Sarwo (Jurnal Hukum dan Peradilan, 2017)
Military Court is the body that conduct the judicial power in the Indonesian Military Force (TNI) scope to enforce law and justice. The Military Court does not culminate and not supervised by the Indonesian Military Force headquarters, but culminates and is supervised by the Supreme Court of the Republic of Indonesia. The Philosophy ofÂ  the occurrence of dependence in the first military justice system, because of the interest of the military (TNI) which is associated with its principal task of TNI is to defend the national sovereignty, for that reason, by putting the role of commander of the unit (Ankum) as well as kepaperaan within the law enforcement system. The Head of the district court also covers Military Court in his jurisdiction because of it the Head of district court becomes the Head of Military Court. The Registrar is automatically also the Registrar of Military Court, Head of State Prosecutors assigned as military prosecutor. These circumstances affect objections which are seen as unfavorable for military or military units. The authority of the Court is no longer based on the rank of the defendant, the hierarchy of court proceedings such as judges, military Prosecutors, defense attorneys, no longer use the rank but wearing a toga. Development of organizational, administrative, financial of Military Courts is fully under the Supreme Court held consequently as stipulated in the law of judicial power.Â  The execution of criminal act by military prison, executed equally as prisoner without discriminating the person by his rank.Keyword: dependency, independency, military justice system